2017
DOI: 10.3233/ch-168010
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and function in response to high intensity interval exercise and moderate continuous exercise in CABG and PCI patients

Abstract: Based on the findings of the present study it could be concluded that the risk of exercise-induced thrombosis is higher during HIIE than MCE in patients with recent revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…In the study by Ahmadizad et al highintensity interval training was found to be higher in patients who underwent new revascularization than in those with continuous revascularization. 28 In our study, while the CRP value did not differ signifi-cantly, we see that the ESR value has decreased. Exercise program has a positive effect to CVS disease by decreasing inflammation.…”
Section: Discussioncontrasting
confidence: 39%
“…In the study by Ahmadizad et al highintensity interval training was found to be higher in patients who underwent new revascularization than in those with continuous revascularization. 28 In our study, while the CRP value did not differ signifi-cantly, we see that the ESR value has decreased. Exercise program has a positive effect to CVS disease by decreasing inflammation.…”
Section: Discussioncontrasting
confidence: 39%
“…[44][45][46] The increase in factor VIII and the degree of platelet activation and aggregation after exercise are associated with the intensity of the exercise. [47][48][49] Furthermore, the degree of platelet activation after HIT is reported to be related to individual physical fitness, leaving untrained individuals in at higher risk than well-trained individuals. 43 4. them more prone to TE events.…”
Section: The Association Of Hit and Te Riskmentioning
confidence: 99%
“…Low levels of cardiorespiratory fitness are associated with platelet hyper-reactivity, and endurance training affects platelet function in terms of normalisation 10. In addition, acute, strenuous exercise causes transient platelet hyper-reactivity,11 which constitutes an underlying mechanism for triggering myocardial infarctions by physical exertion 12. In this regard, evidence suggests that regular exercise training performed over several weeks can diminish transient platelet hyper-reactivity after acute exertion in healthy individuals 13…”
Section: Introductionmentioning
confidence: 99%